LRPPRC facilitates tumor progression and immune evasion through upregulation of m6A modification of PD-L1 mRNA in hepatocellular carcinoma - Wang, Houhong; Tang, Amao; Cui, Yayun; Gong, Huihui; Li, Heng (Frontiers in Immunology, 2023)
Objective LRPPRC is a newly discovered N6-methyladenosine (m6A) modification reader, which potentially affects hepatocellular carcinoma (HCC) progression. PD-L1 in tumor cells is essential for tumor immune evasion. This work investigated the LRPPRC-mediated m6A-modification effect on PD-L1 mRNA and immune escape in HCC. Methods Expression and clinical implication of LRPPRC and PD-L1 were measured in human HCC cohorts. The influence of LRPPRC on malignant behaviors of HCC cells was investigated through in vitro assays and xenograft tumor murine models. The posttranscriptional mechanism of LRPPRC on PD-L1 and anti-tumor immunity was elucidated in HCC cells via RIP, MeRIP−qPCR, RNA stability, immunohistochemical staining, and so forth. Results LRPPRC exhibited the notable upregulated in human HCC tissues, which was in relation to advanced stage and worse overall survival and disease-free survival. Impaired proliferative capacity and G2/M phage arrest were found in LRPPRC-knockout cells, with increased apoptotic level, and attenuated migratory and invasive abilities. In HCC patients and murine models, LRPPRC presented a positive interaction with PD-L1, with negative associations with CD8+, and CD4+ T-cell infiltrations and chemokines CXCL9, and CXCL10. LRPPRC loss downregulated the expression of PD-L1 and its m6A level in HCC cells. Moreover, LRPPRC suppression mitigated tumor growth in murine models and improved anti-tumor immunity and immune infiltration in tumors. Conclusion This work unveiled that LRPPRC may posttranscriptionally upregulate PD-L1 partially with an m6A-dependent manner for heightening mRNA stabilization of PD-L1 and provided a new mechanism for m6A regulator-mediated immunosuppression in HCC.